2018
DOI: 10.1097/ico.0000000000001784
|View full text |Cite
|
Sign up to set email alerts
|

Two Femtosecond Laser LASIK Platforms: Comparison of Evolution of Visual Acuity, Flap Thickness, and Stromal Optical Density

Abstract: Purpose: To compare postoperative evolution of visual acuity, flap thickness, and stromal optical density during the first 3 months after femtosecond (FS) laser in situ keratomileusis surgery for correction of myopia using the iFS 150-kHz FS laser and LenSx FS laser platforms. Methods: This was a prospective case series. Thirty-nine eyes treated with the iFS 150-kHz FS laser versus 38 refraction-matched eyes treated with the LenSx FS laser platform were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Notably, data from a past study among experienced and novice LASIK surgeons indicated a fellowship-training program based on a standardized surgical protocol to result in statistically comparable outcomes between an expert surgeon and a fellowship-trained surgeon when newly transitioned from mechanical microkeratome to a FS laser flap creation. [20] However, it should be noted that, while FS laser-created LASIK flap has been reported to be a uniform flap that may contribute to more predictable refractive and wavefront outcomes, [5,9,21] the clinical relevance of FS laser is considered to remain controversial. [5,19] In a past study comparing iFS 150-kHz vs. LenSx FS lasers in correction myopia, authors reported association of iFS 150 kHz with significantly lower intra-FT range at…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, data from a past study among experienced and novice LASIK surgeons indicated a fellowship-training program based on a standardized surgical protocol to result in statistically comparable outcomes between an expert surgeon and a fellowship-trained surgeon when newly transitioned from mechanical microkeratome to a FS laser flap creation. [20] However, it should be noted that, while FS laser-created LASIK flap has been reported to be a uniform flap that may contribute to more predictable refractive and wavefront outcomes, [5,9,21] the clinical relevance of FS laser is considered to remain controversial. [5,19] In a past study comparing iFS 150-kHz vs. LenSx FS lasers in correction myopia, authors reported association of iFS 150 kHz with significantly lower intra-FT range at…”
Section: Discussionmentioning
confidence: 99%
“…[ [3][4][5] Thus, the technological evolution of flap creation has emerged from manually guided mechanical microkeratomes to automated microkeratomes, single-use microkeratomes, and most recently to femtosecond (FS) laser technology. [3,6,7] In 2015, a new software program was installed to the original software of the LenSx FS laser to perform LASIK flaps via the same FS laser previously used for cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations